Analisis Pelaksanaan Ujian Sekolah Berbasis Android (USBA) - Ricky Herpana Putra; Menik Kurnia Siwi (Jurnal Ecogen, 2021)
This study aims to determine the implementation of the Android-Based School Examination (USBA) at SMAN 3 Sungai Penuh. This type of research is descriptive with a qualitative approach. Data collection techniques by interview and documentation. The data sources used were primary data and secondary data, which were analyzed by using triangulation techniques. The number of informants in this study were 6 people, namely USBA operators and class XII students of SMAN 3 Sungai Penuh. The results showed that the USBA implementation process at SMAN 3 Sungai Penuh was the same as the conventional exam implementation process, but at USBA students were more independent. The advantages of USBA include exams that can be done anywhere, USBA costs are more efficient than paper exams, test results can be seen after students have finished taking exams, with this USBA minimizing the occurrence of cheating by students. Constraints in implementing USBA are the low capacity of the internet network. Comparing conventional exams with USBA, there are many differences between the two, this can be seen from the equipment used, the form of the questions, the time for taking the questions, the place and the operational costs of the exam.